Tributyrin Plays an Important Role in Regulating the Growth and Health Status of Juvenile Blunt Snout Bream (Megalobrama amblycephala), as Evidenced by Pathological Examination - Liang, Hualiang; Ji, Ke; Ge, Xianping; Xi, Bingwen; Ren, Mingchun; Zhang, Lu; Chen, Xiaoru (Frontiers in Immunology, 2021)
The present study aimed to assess the role of tributyrin (TB) in regulating the growth and health status of juvenile blunt snout bream (Megalobrama amblycephala) through an 8-week feeding experiment. Six groups were fed experimental diets with added TB percentages of 0% (control group), 0.03%, 0.06%, 0.09%, 0.12% and 0.15%. The present results showed that TB supplementation in feed had some positive impacts on FW, WG, FCR and SGR, and the best results were found in the 0.06% TB group (P<0.05). However, TB supplementation in feed had no significant effects on SR, CF, VSI or whole-body composition (P>0.05). TB supplementation in feed increased antioxidant capacity and immunological capacity and attenuated the inflammatory response by increasing the activity of T-SOD, GPx, CAT and the levels of anti-inflammatory cytokines (IL-10 and TGF-β) and decreasing the levels of MDA and anti-inflammatory cytokines (TNF-α) (P<0.05). Furthermore, TB supplementation improved immunity by increasing the levels of immunoglobulins (IgM and IgG), C3 and IFN-γ (P<0.05). Surprisingly, 0.06%-0.12% TB supplementation significantly increased the content of IL-1β (P<0.05). However, TB supplementation in feed had no significant effects on the plasma content of GSH, HSP70, IL-8 and the activity of T-AOC (P>0.05). The possible mechanism was that TB activated PI3K/Akt/Nrf2 and inhibits the NF-κB signaling pathway, further regulating the mRNA levels of key genes with antioxidant capacity and the inflammatory response; for example, it increased the mRNA levels of Nrf2, Cu/Zn-SOD, HO-1, CAT, Akt, PI3K, GPx, IL-10, and TGF-β and decreased the mRNA levels of NF-κB and TNF-α (P<0.05). In addition, 0.06%-0.15% TB supplementation significantly increased the mRNA levels of IL-1β (P<0.05). TB supplementation in feed had no significant effects on the mRNA levels of HSP70, Mn-SOD and IL-8 (P>0.05). Evidence was presented that TB supplementation decreased the mortality rate caused by Aeromonas hydrophila challenge. In pathological examination, TB supplementation prevented hepatic and intestinal damage. Generally, TB supplementation improved the growth performance of juvenile blunt snout bream. Furthermore, TB supplementation activated PI3K/Akt/Nrf2 and inhibited the NF-κB signaling pathway, regulating health status and preventing hepatic and intestinal damage.